2022
DOI: 10.1007/s11661-021-06549-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nucleant Particle Agglomeration on Grain Size

Abstract: Solute accumulation/depletion in the liquid around a growing solid particle during the solidification of metallic melts creates a constitutionally supercooled (CS) zone that has a significant effect on the final solidified grain structure. In this paper, we introduce two mechanisms related to the CS zone that affect grain size: one is the grain initiation free zone (GIFZ) that describes the inability of nucleant particles located in the CS zone for grain initiation and the other is re-melting (RM) of solid par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…However, when increasing the inoculant concentration from 5 wt% to 10 wt%, only a minor improvement was noted. Agglomeration of the inoculant particles was found to be detrimental for the potency of the inoculants in providing grain refinement [55]. Liu et al [56] and Yang et al [57] observed that the potency of the inoculant particles as grain refiner reduced after reaching a critical value.…”
Section: Tib 2 As An Inoculant For Ded In718mentioning
confidence: 99%
“…However, when increasing the inoculant concentration from 5 wt% to 10 wt%, only a minor improvement was noted. Agglomeration of the inoculant particles was found to be detrimental for the potency of the inoculants in providing grain refinement [55]. Liu et al [56] and Yang et al [57] observed that the potency of the inoculant particles as grain refiner reduced after reaching a critical value.…”
Section: Tib 2 As An Inoculant For Ded In718mentioning
confidence: 99%
“…The operating temperature in the LPT section is typically below the intensive creep range [ 14 ]. To address this issue, castings generally are modified by adding refiners, which contain highly stable particles, or by introducing an inoculant to the prime coat of the ceramic mold [ 15 , 16 ]. Grain refinement in the primary microstructure is directly related to increased heterogeneous nucleation sites during solidification [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, after a certain contact time, the grain refining effect of master alloy additions fades, which phenomenon is commonly attributed to the sedimentation, agglomeration, or dissolution of the introduced nucleant particles. Another possibility for reduced refining efficiency is the so-called poisoning effect when an alloying element or impurity reduces the heterogeneous nucleation potency of the introduced particles [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%